Validitas Media Mobile Learning Ensiklopedia Alat Musik Tradisional dalam Penguatan Literasi Budaya Siswa Sekolah Dasar - Saskia Handayani Aristya Regina Putri; Wendri Wiratsiwi (Lembaga Pengembangan Kinerja Dosen, 2026)
Traditional musical instruments are a national heritage that needs to be taught to elementary school students. However, the low cultural literacy regarding traditional musical instruments among fourth-grade students at UPT SD Negeri Dikir is caused by the use of science and social studies (IPAS) learning media that remain static and conventional, making it difficult for students to recognize the identity and sound characteristics of regional music. This study aims to determine the validity of mobile learning media in the form of a traditional musical instrument encyclopedia for fourth-grade IPAS learning on the topic of traditional musical instruments. This research utilized the ADDIE model, which includes analysis, design, development, implementation, and evaluation; however, the study was limited to the development stage. Media validity was obtained through assessments by material experts, language experts, and media experts using validation sheets. The results showed that the material expert assessment scored 89.5%, the language expert scored 85%, and the media expert scored 75%, all falling into the highly valid category. The overall average score reached 84%, indicating that the mobile learning media in the form of a traditional musical instrument encyclopedia is declared highly valid and feasible for use in the learning process of elementary school IPAS, specifically for traditional musical instruments material.